PHYTOCHEMICAL ANALYSIS AND TOTAL TANNIN CONTENT (TTC) OF DELONIX REGIA (BOJER EX. HOOK) RAF. BARK BY USING DIFFERENT SOLVENTS COLLECTED FROM SAURASHTRA REGION (International Association of Biologicals and Computational Digest, 2022)
Delonix regia (Bojer ex. hook) Raf. is belongs to Leguminosae (Fabaceae) family and Sub family Caesalpiniodeae. Usually it’s called gulmahor in Gujarati. It is used as an ornamental plant but it has some bioactive constituents which are useful in medicinal level. Delonix regia (Bojer ex. hook) Raf. is a beautiful, semi-deciduous and roadside avenue tree. It is cultivated in rural and urban area in India. It has medicinal properties such as antimicrobial and antifungal activities or as antibiotics. In this present study, qualitative and quantitative estimation of Delonix regia (Bojer ex. hook) Raf. bark from Saurashtra region. The preliminary phytochemical analysis and quantification for total tannin content was performed by using two different solvents (Acetone and Ethanol). The phytochemical analysis revealed that the presence of various phytochemicals such as phenols, tannins, flavonoids, proteins etc. Based on experiment, various bioactive constituents were present so it’s important for pharmaceutical level.
Keywords: Fabaceae, Tannin, quantitative analysis, Delonix